Cadmium Tolerance of Perennial Ryegrass Induced by Aspergillus aculeatus - Han, Shijuan; Li, Xiaoning; Amombo, Erick; Fu, Jinmin; Xie, Yan (Frontiers in Microbiology, 2018)
Cadmium (Cd) pollution is becoming increasingly prevalent, posing a global environmental hazard due to its negative effects on plants growth and human health. Phytoremediation is a green technology that involves uptake of Cd from the soil by a combination of plants and associated microbes. The objective of this study was to investigate the role of Aspergillus aculeatus in perennial ryegrass Cd tolerance. This fungus produced indole-3-acetic acid, siderophores and 1-aminocyclopropane-1-carboxylate deaminase. Physiological traits including growth rate, turf quality and chlorophyll content were measured to evaluate the physiological responses of perennial ryegrass to Cd stress. These physiological traits were improved after inoculated with Aspergillus aculeatus. Inoculation of Aspergillus aculeatus actively reduced DTPA-Cd concentration in the soil and Cd translocation to plant shoots. Chlorophyll a fluorescence transient and the C/N ratio in shoots were elevated by Aspergillus aculeatus, which implied that the fungus could protect the photosystem II against Cd stress andincrease the photosynthetic efficiency. These results suggested that Aspergillus aculeatus is beneficial in improving Cd tolerance of perennial ryegrass and reducing Cd-induced injuries, thus, has promising potential for application in phytostabilization in Cd contaminated soil.